In vitro Hepatoprotective potential of the whole plant of Fumaria indica (Haussk.) Pugsley and an isolated alkaloid Protopine - Anagha Arun Rajopadhye; Anuradha S. Upadhye (International Journal of Phytomedicine, 2020)
Fumaria indica (Haussk.) Pugsley, Fumariaceae [syn. F. vaillantii Loisel.] is an important medicinal plant known as ‘Fumitory’. Ethnobotanical and ayurvedic literature reports that the plant is used in treatment of liver diseases as well as diverse pharmacological activities. In present work, in vitro hepatoprotective effects of ethanol extract of F. indica (FUP) and alkaloid, protopine (PRT) on carbon tetrachloride induced oxidative stress has been demonstrated. An isoquinoline alkaloid, protopine was isolated from ethanol extract of F. indica and characterized by spectral data. Carbon tetrachloride (CCl4) and ethanol has been used as a hepatotoxin. Cytotoxicity was estimated by quantitating the release of lactate dehydrogenase (LDH) in culture medium along with antioxidant enzymes namely superoxide dismutase, catalase and glutathione reductase. HPLC profile of FUP and PRT was developed using water: methanol (7:3) as a mobile phase. CCl4 and ethanol induces 5.5 and 4 times more release of LDH from the liver cells and twice the amount of lipid peroxidation as compared to the cells from untreated liver tissue. These LDH and lipid perioxidation activities were reduced significantly in dose dependent manner after addition of FUP and PRT (at doses 0.5 % FUP and at does 0.025, 0.05 % PRT; p < 0.001). The activity of antioxidant enzymes was found to be elevated in CCl4/ethanol treated cells. However, after addition of FUP/PRT along with cytotoxicant the activities were lowered significantly. The peak of PRT has been detected in FUP at retention times 1.670. sBased on these studies it may be precluded that protopine from F. indica, as a possible therapeutic for preventing oxidative stress in vitro by boosting the antioxidant capacity of the liver.